Effect of internal and external remittances on expenditure inequality in Pakistan - Waqas Shair; Mumtaz Anwar (Cogent Economics & Finance, 2023)
The impact of remittances on household expenditure inequality is extensively documented in the development literature. Yet, it is relatively less focused on its effect at the household level. In the context of Pakistan, higher labour migration offers enough scope to examine the expenditure inequality across the remittance-receiving and non-receiving households. This study analyzes the effect of external and internal remittances on expenditure inequality of households in Pakistan. The study uses data from PSLM-HIES 2018-2019 survey. The quantile regression results suggest an unequal expenditure distribution across the household. The external remittance-receiving household is significantly higher in expenditure per capita across the distribution vis-à-vis internal migrant or without migrant households. The study concluded that the current level of endowment is higher in the external remittance-receiving household, which is a significant source of expenditure gap across the household categories. The aftermath of the mean decomposition model suggests that the relatively higher income of the external remittance-receiving household significantly contributes to the expenditure gap across the household categories. The findings from quantile decomposition suggest that external remittances cause more discrimination for the affluent household than the poor ones. The study's implication suggests some policy measures to ease the access to international migration to improve the expenditure distribution.
Keywords: 330; expenditure inequality; external remittances; internal remittances; Pakistan